Comparison of behaviour between rebar and stud shear connectors under monotonic loading - Saravanakumar, B.; Thenmozhi, R. (Journal of Structural Engineering, 2024)
In composite beams, shear connectors are commonly used to transfer longitudinal shear forces across the steel–concrete interface. The shear connectors also prevent relative displacement of concrete and steel elements at their interface and ensure composite action of the beam. Presently, the stud is the most widely used shear connector in composite constructions. However, the rebar can be used as a shear connector according to various international codes considering the fact that it can be fabricated to the required shape along with the reinforcement cage in the slab. This paper presents an experimental study of the behaviour of rebar shear connectors embedded in composite beam under monotonic load. Two different (8mm and 10mm) diameter rebar connectors of four different forms such as open link, closed stirrups, circular and rectangular spiral were used as shear connectors. Modified push-out tests were conducted to assess the ultimate strength, elastic stiffness, load-slip characteristics and failure pattern of the rebar shear connectors and the same are compared with conventional stud shear connectors. Rebar shear connector with circular spiral shows higher ultimate strength and superior ductile behaviour compared to conventional stud shear connector.